Divergent Thinking Abilities in Frontotemporal Dementia: A Mini-Review - Fusi, Giulia; Crepaldi, Maura; Colautti, Laura; Palmiero, Massimiliano; Antonietti, Alessandro; Rozzini, Luca; Rusconi, Maria Luisa (Frontiers in Psychology, 2021)
A large number of studies, including single case and case series studies, have shown that patients with different types of frontotemporal dementia (FTD) are characterized by the emergence of artistic abilities. This led to the hypothesis of enhanced creative thinking skills as a function of these pathological conditions. However, in the last years, it has been argued that these brain pathologies lead only to an augmented “drive to produce” rather than to the emergence of creativity. Moreover, only a few studies analyzed specific creative skills, such as divergent thinking (DT), by standardized tests. This Mini-Review aimed to examine the extent to which DT abilities are preserved in patients affected by FTD. Results showed that DT abilities (both verbal and figural) are altered in different ways according to the specific anatomical and functional changes associated with the diverse forms of FTD. On the one hand, patients affected by the behavioral form of FTD can produce many ideas because of unimpaired access to memory stores (i.e., episodic and semantic), but are not able to recombine flexibly the information to produce original ideas because of damages in the prefrontal cortex. On the other hand, patients affected by the semantic variant are impaired also in terms of fluency because of the degradation of their semantic memory store. Potential implications, limitations, and future research directions are discussed.